IMPLEMENTASI PENGEMBANGAN ENERGI BARU TERBARUKAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) OLEH DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI SUMATERA BARAT DI SOLOK SELATAN - Givan Dwi Guna; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aims to determine the Renewable Energy Development Implementation in South Solok Regency. New and Renewable Energy is clean energy that is rich in diversity and quantity such as solar energy, wind, natural gas, ocean waves, garbage, wood, biomass, nuclear and water (microhydro). New and Renewable Energy was developed by the West Sumatra Provincial ESDM Office in the South Solok area since 2013, however, in implementing this development there were still some obstacles which was faced by the West Sumatra Provincial ESDM Office as the community which has not felt the impact of developing the benefits of PLTMH. It was because there were some PLTMH which were not functioning or have damaged caused by natural disasters such as floods and landslides, there was still a lack of technicians to repair the damage to the PLTMH, there was still a lack of costs obtained from PLTMH customers who aimed to repair damage to PLTMH generators and turbines. This study was a qualitative research which used descriptive method. The research respondents were selected by using a purposive sampling technique. For the data collection, this study used interview guidelines, observation, and documentation of the research as the instrumentation. The validation technique used the triangulation method. Furthermore, the data analysis technique was reducing data, displaying data, and drawing the conclusions of the study which has been conducted. The findings showed that the Renewable Energy Development implementation for Micro Hydro Power Plants (PLTMH) by the ESDM Office of West Sumatra Province in South Solok was still not running as it should be, because there were still some obstacles which were faced in developing of New Renewable Energy of PLTMH that the results was not being implemented properly. Supporting factors for the implementation of this PLTMH development were the data and information, communication, bureaucratic attitudes, and organizational structure. While communication, organizational characteristics, economic environment and human resources were the inhibiting factors. The Effort to overcome these obstacles was the government has signed several commitments related to the development of Renewable Energy. Beside that, to fill the conditions of the national electricity, the government has also involved the private sector